Biogenic silver nanoparticles mediated by Broussonetia papyrifera: anticancer and antimicrobial activity against pathogenic organisms - N, Vasanth; G, Melchias; P, Kumaravel (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the potential aspects of biologically synthesized silver nanoparticles mediated by Broussonetia papyrifera against the human pathogens. The same is acknowledged to have high efficiency in the field of Pharmaceutical industry. Methods: The 1Mm of AgNO3 is prepared and mixed with appropriate volume of plant extract and reaction volume was made up to 100 ml. the physical characterization of AgNPs was done. The anti-microbial activity was done against dread pathogens. Cytotoxic activity of the AgNPs was investigated against breast and lung cancer cell lines. Results: The FESEM and EDAX of the microscopic level showed the particle surface measurements around 44 nm to 50 nm. The XRD investigations are being an evidence for the crystalline structure of the AgNPs with 30 nm. The bacterial pathogen Rhodococcus rhodochrous showed the maximum zone of inhibition (11.8±0.447). The A549 human lung cancer cell line and MCF-7 human breast cancer cell line were tested against the toxicity of AgNPs. The toxicity of AgNPs was valued and corresponding IC50 for Lung cancer (A549) is 12.95± 0.05 µg/mL and Breast cancer (MCF-7) is 10.75± 0.05 µg/mL respectively. Conclusion: The present research denotes that biomolecules derived AgNPs have larger impact as antimicrobials in the biomedical field. Since the aggressive chemicals are not involved AgNPs production, these bio-substances can of alternative medicine to resistant once. The in-vitro experiments exhibits the therapeutic effect of this AgNPs based on the ambient concentration on the process.